-35x=100x+27

Simple and best practice solution for -35x=100x+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -35x=100x+27 equation:


Simplifying
-35x = 100x + 27

Reorder the terms:
-35x = 27 + 100x

Solving
-35x = 27 + 100x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-100x' to each side of the equation.
-35x + -100x = 27 + 100x + -100x

Combine like terms: -35x + -100x = -135x
-135x = 27 + 100x + -100x

Combine like terms: 100x + -100x = 0
-135x = 27 + 0
-135x = 27

Divide each side by '-135'.
x = -0.2

Simplifying
x = -0.2

See similar equations:

| 8x+6=-34 | | -3y-9=2y+11 | | 5/10= | | -4n+9=n-1 | | -13=x+14 | | 24-x=7 | | 5(7x-2)=33x | | -7(2b-4)=5(-2+6) | | 2(y+3)=2y+6 | | 25c^2-1=0 | | 5m-3m=2 | | 5(2x-3)=8x-15 | | -5x-6=29 | | -10x=130 | | 8(x+6)=7(x+8) | | 11=-8x+51 | | 60+5w=135-10w | | 36w^2-77w-9=0 | | 8-10x=82 | | 4x-8y+8=0 | | 44=-x | | n-6(1-5n)=-161 | | 16-x=26 | | 4(x-9)=3x-8x | | 0.75x-(9+x)=31 | | 9x=8x-3 | | 3(5+3x)-47x= | | -2(3x+8)-3=24 | | 2t-3t+8t=7t | | 7-Du=5u+29 | | s+(3s+.22)+(s-.12)=4.6 | | 5x+6+2x-1=10x+13 |

Equations solver categories